2021
DOI: 10.1371/journal.pone.0253048
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and evidence-based management of needle fear in adults with chronic disease: A scoping review

Abstract: Background Little is known about the prevalence and best management of needle fear in adults with chronic disease, who may experience frequent and long-term exposure to needles for lifesaving therapies such as renal dialysis and cancer treatment. Identifying interventions that assist in management of needle fear and associated distress is essential to support these patients with repeated needle and cannula exposure. Method We followed the PRISMA methodology for scoping reviews and systematically searched Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…In 2007, a large US-based survey evaluated the epidemiology of needle phobia using the DSM criteria and reported a strikingly low prevalence (2.1%) of BII phobia in the total adult population [ 16 ]. On the other hand, a review of the literature focusing on adults with different chronic diseases used a broader definition as discomfort, anxiety, fear, distress and/or phobia related to needles [ 22 ]. The study reported higher rates of needle fear, with prevalence ranging from 17% to 52% among adults with past or current experience of chemotherapy and from 25% to 47% among adults receiving peritoneal dialysis or hemodialysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, a large US-based survey evaluated the epidemiology of needle phobia using the DSM criteria and reported a strikingly low prevalence (2.1%) of BII phobia in the total adult population [ 16 ]. On the other hand, a review of the literature focusing on adults with different chronic diseases used a broader definition as discomfort, anxiety, fear, distress and/or phobia related to needles [ 22 ]. The study reported higher rates of needle fear, with prevalence ranging from 17% to 52% among adults with past or current experience of chemotherapy and from 25% to 47% among adults receiving peritoneal dialysis or hemodialysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple innovation-related (e.g., using smaller/thinner needles or autoinjectors) [ 17 – 21 ] and other strategies (e.g., educational and psychological interventions) [ 22 , 23 ] to address needle phobia were presented in the literature. However, these assessments were generally limited to evaluating a single approach without comparing different approaches/strategies to address needle fear.…”
Section: Introductionmentioning
confidence: 99%
“…Although concerns about injectable medications are well established among both people with diabetes and clinicians (30), clinicians should strive to be a catalyst for overcoming, rather than propagating, any concerns on the part of people with diabetes. One helpful strategy is to have people self-administer their first dose of an injectable GLP-1 receptor agonist in the clinic and then ask if they have any concerns with the experience.…”
Section: Strategies To Resolve Barriers (Video 4)mentioning
confidence: 99%
“…[11][12][13] Despite good clinical efficacy, patients are often reluctant to repeated needle injections due to associated pain, needle fatigue, and needle phobia. 14 Additionally, the treatment is hard to standardize, and outcomes heavily rely on the practitioner's experience.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the combination of corticosteroids and the antiproliferative agent 5‐fluorouracil (5‐FU) demonstrated better efficacy and safety profile compared to corticosteroids alone 11–13 . Despite good clinical efficacy, patients are often reluctant to repeated needle injections due to associated pain, needle fatigue, and needle phobia 14 . Additionally, the treatment is hard to standardize, and outcomes heavily rely on the practitioner's experience.…”
Section: Introductionmentioning
confidence: 99%